Effects of particle uptake, encapsulation, and localization in cancer cells on intracellular applications. Issue 5 (May 2015) - Gal, N.; Massalha, S.; Samuelly-Nafta, O.; Weihs, D.
Highlights Endocytosis is affected by cell function, and likely malignancy. Particles endocytose into cells with reduced cell–cell interactions. Endocytosed particles may become unencapsulated by membranes with time. Endocytosis can safely be used to internalize particles for tracking.